2020
DOI: 10.3390/ijms21207651
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Circulating Tumor DNA Liquid Biopsy in Pancreatic Cancer

Abstract: Pancreatic cancer is a challenging disease with a low 5-year survival rate. There are areas for improvement in the tools used for screening, diagnosis, prognosis, treatment selection, and assessing treatment response. Liquid biopsy, particularly cell free DNA liquid biopsy, has shown promise as an adjunct to our standard care for pancreatic cancer patients, but has not yet been universally adopted into regular use by clinicians. In this publication, we aim to review cfDNA liquid biopsy in pancreatic cancer wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 97 publications
4
27
0
Order By: Relevance
“…Combined with circulating tumor cells (CTCs) analysis, it may represent a tool to assess in real-time both tumor burden and molecular features of the disease [ 94 ]. ctDNA has been studied in patients with various cancer types, including advanced pancreatic cancer [ 95 , 96 ]. A recent meta-analysis including 19 studies further evaluates ctDNA and other liquid biopsy diagnostics, such as CTSs and blood exosomes, in PDAC detection [ 97 ].…”
Section: New Perspectivesmentioning
confidence: 99%
“…Combined with circulating tumor cells (CTCs) analysis, it may represent a tool to assess in real-time both tumor burden and molecular features of the disease [ 94 ]. ctDNA has been studied in patients with various cancer types, including advanced pancreatic cancer [ 95 , 96 ]. A recent meta-analysis including 19 studies further evaluates ctDNA and other liquid biopsy diagnostics, such as CTSs and blood exosomes, in PDAC detection [ 97 ].…”
Section: New Perspectivesmentioning
confidence: 99%
“…In the last years, cell-free tumor DNA (ctDNA) has been acquiring a great relevance for precision medicine, since it allows us to perform a molecular characterization of the tumor in a less invasive manner and to overcome issues related to tumor heterogeneity. Although few data are available, the analysis of ctDNA could provide several advantages in clinical practice of PDAC [40] and it should be useful also for the evaluation of BRCA1/2 gene mutations, particularly when tumor tissue is not available or adequate. Moreover, interesting data have been published about the possibility to evaluate on ctDNA also BRCA1/2 reversion mutations to predict primary and acquired resistance to PARP inhibitors [41].…”
Section: Discussionmentioning
confidence: 99%
“…The relatively low sensitivity however may have been due to the abundance of ctDNA in the circulation[ 20 ]. It has been found that the abundance of ctDNA has a positive correlation with tumour load, supported by the physiology of ctDNA mentioned above: It is released through cell death[ 22 ]. Due to this, ctDNA may not be an ideal candidate for use in early detection of PDAC but may have a role as a prognostic biomarker or a marker of response to treatment, especially in those that are CA19-9 negative.…”
Section: Biomarker Discoverymentioning
confidence: 97%